Changes in Structural, Physicochemical, and Functional Properties of Germ Rice during Germination - Lele LU; Qin SHEN; Shilin LIU; Baijun WANG; Shuangjing LANG; Lidong WANG; Changyuan WANG (Shipin gongye ke-ji)
In this investigation, germ rice derived from Daohuaxiang was utilized to examine the alterations in morphology, structure, and functional properties of germ rice throughout the germination process. The obtained germ rice was germinated for varying durations of 0, 12, 24, 36 and 48 h. The changes of germ rice during germination were analyzed by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) analysis methods. The findings revealed a significant increase (P<0.05) in amylase activity at 12 h post-germination, accompanied by a 10.86% reduction in total starch content after 48 h. Furthermore, there was an initial rise followed by a decline in amylose content. Notably, the estimated glycemic index exhibited a decrease of 3.3. Following 36 h of germination, the peak gamma-aminobutyric acid content reached 138.09 mg/100 g, marking a 6.89-fold increase compared to pre-germination levels. After 48 h of germination, the contents of free polyphenols and free flavonoids were measured at 103.98 mg/100 g and 53.12 mg/100 g, respectively, reflecting a rise of 90.75% and 24.93% from untreated samples. Notably, the antioxidant capacities, as measured by DPPH, ABTS, T-AOC and FRAP assays, which initially stood at 5.37%, 2.70%, 6.37 U/mg and 0.48 mmol Fe2+/g, exhibited notable enhancements of 158.29%, 169.63%, 41.92% and 14.58%, respectively, following 48 h of germination. Simultaneously, post-germination, a noticeable passivation of the cavity structure of aleurone cells was observed, accompanied by the ongoing hydrolysis of macromolecules like starch and protein in the germ rice. These processes led to the relaxed rice structure, reduced starch crystallinity, and order. The research findings affirm that germination treatment can decrease eGI and increase the content of γ-aminobutyric acid, thereby laying a theoretical basis for the development of more versatile rice and nutritious rice and the research of germinated rice products.